2014
DOI: 10.1007/s10637-014-0154-x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase III trial of regorafenib in metastatic colorectal cancer: analysis of the CORRECT Japanese and non-Japanese subpopulations

Abstract: SummaryBackground In the international, phase III, randomized, double-blind CORRECT trial, regorafenib significantly prolonged overall survival (OS) versus placebo in patients with metastatic colorectal cancer (mCRC) that had progressed on all standard therapies. This post hoc analysis evaluated the efficacy and safety of regorafenib in Japanese and non-Japanese subpopulations in the CORRECT trial. Methods Patients were randomized 2 : 1 to regorafenib 160 mg once daily or placebo for weeks 1–3 of each 4-week c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
97
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 14 publications
12
97
4
2
Order By: Relevance
“…The dose intensity of Reg was lower in Japanese compared with that in non-Japanese patients, as dose modifications due to AEs were more frequent in the Japanese group. The rate of treatment discontinuation due to Reg-associated AEs was also higher in the Japanese group (15). When Reg was launched in May, 2013, treatment was initiated at the dose of 160 mg.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The dose intensity of Reg was lower in Japanese compared with that in non-Japanese patients, as dose modifications due to AEs were more frequent in the Japanese group. The rate of treatment discontinuation due to Reg-associated AEs was also higher in the Japanese group (15). When Reg was launched in May, 2013, treatment was initiated at the dose of 160 mg.…”
Section: Discussionmentioning
confidence: 97%
“…However, AEs such as HFSR, hypertension, thrombocytopenia and proteinuria occurred at a higher incidence among Japanese patients, and it was also reported that 1 Japanese patient succumbed to liver dysfunction due to Reg. In addition, dose modifications due to AEs were more frequent and the dose intensity of Reg was lower in Japanese compared with that in non-Japanese patients (15). Therefore, although Reg achieved clinical benefits with tolerable AEs according to previous studies (14,16), its efficacy and safety in Japanese patients should be verified in the clinical setting.…”
Section: Introductionmentioning
confidence: 95%
“…The most frequent regorafenib-related AEs of grade ≥3 in the CORRECT trial were hand-foot skin reaction, fatigue, diarrhea, hypertension and rash or desquamation (2). Regarding the incidence of regorafenib-related hepatotoxicity, including hyperbilirubinaemia and elevation of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels, it was relatively low in a non-Japanese population, while it was high in a Japanese population (5). These results were supported with the CONCUR trial (3), which was performed by institutions in Asia.…”
Section: Introductionmentioning
confidence: 85%
“…One of the most common adverse events associated with Regorafenib is Hand-foot Skin Reaction (HFSR). In the CORRECT study, HFSR occurred at a rate of 44.6% overall and 16.6% at grade 3 [2], and showed higher proportions (80 and 27.7%, respectively) in the Japanese subpopulation [3]. HFSR is not life-threatening adverse event, but may cause considerable deterioration of patients' Quality of Life (QOL), resulting in discontinuation of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…HFSR associated with TKIs occurs earlier compared with cytotoxic anticancer agents (fluoropyrimidines or taxanes). Patients with TKIs-associated HFSR often present with erythema, swelling, bullae, and hyperkeratosis, especially in pressure-bearing skin surface such as plams or soles [3][4][5][6][7][8][9][10][11]. Although there are no established therapeutic options available for TKIs-associated HFSR, it has recommended that pressure bearing should be avoided in daily life [4].…”
Section: Introductionmentioning
confidence: 99%